2016
DOI: 10.1186/s12877-016-0289-z
|View full text |Cite
|
Sign up to set email alerts
|

Systems to identify potentially inappropriate prescribing in people with advanced dementia: a systematic review

Abstract: BackgroundSystems for identifying potentially inappropriate medications in older adults are not immediately transferrable to advanced dementia, where the management goal is palliation. The aim of the systematic review was to identify and synthesise published systems and make recommendations for identifying potentially inappropriate prescribing in advanced dementia.MethodsStudies were included if published in a peer-reviewed English language journal and concerned with identifying the appropriateness or otherwis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…The PEACE criteria categories offer a 'one size fits all' approach to identifying inappropriate medications and do not take into account clinical factors and context that may be at play in individual cases. Holmes et al (2008) identified a need for future research focusing on larger sample populations which can better showcase the relationship between comorbidities and medication use, as well as identify distinct medication classes that may be overused 14 . Dependence on IDEAL Study data meant that some variables found predictive by previous studies (especially those at the nursing home level) could not be included in the current analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PEACE criteria categories offer a 'one size fits all' approach to identifying inappropriate medications and do not take into account clinical factors and context that may be at play in individual cases. Holmes et al (2008) identified a need for future research focusing on larger sample populations which can better showcase the relationship between comorbidities and medication use, as well as identify distinct medication classes that may be overused 14 . Dependence on IDEAL Study data meant that some variables found predictive by previous studies (especially those at the nursing home level) could not be included in the current analyses.…”
Section: Discussionmentioning
confidence: 99%
“…12 A recent systematic review identified only one currently available dementia-specific criteria for identifying potentially inappropriate medications, which were developed through the Palliative Excellence in Alzheimer Care Efforts Program (PEACE) 13 and classify medications as 'never', 'rarely', 'sometimes' or 'always' appropriate based on a Delphi process carried out with 12 geriatricians. 14 Six international studies have used these criteria to examine the prevalence of inappropriate prescribing in nursing home residents with advanced dementia and associated factors. [15][16][17][18][19][20] These studies were undertaken in European countries, [17][18][19] the USA 15,16 and Canada, 20 and found that proportions of nursing home residents with advanced dementia receiving 'never' appropriate medications ranged from 3% 17 to 45% 20 of study populations.…”
Section: Introductionmentioning
confidence: 99%
“…Data suggest that older adults with dementia are commonly prescribed potentially unsafe medications. [2][3][4] Deprescribing refers to supervised tapering or cessation of drugs, aiming to minimize inappropriate polypharmacy and improve patient outcomes. 2 Most research on potentially inappropriate prescribing is focused on the elderly in general rather than dementia specifically.…”
Section: Dear Editormentioning
confidence: 99%
“…3 However, studies are increasingly focusing on prescribing in people with dementia. The PEACE program 4 has produced criteria that seem promising in terms of identifying potentially inappropriate medications in advanced dementia, including anticholinesterase inhibitors and lipid-lowering agents. There is a growing body of evidence showing that discontinuing specific medications in certain patient populations does not worsen outcomes.…”
Section: Dear Editormentioning
confidence: 99%
“…As dementia progresses, cognitive and physical decline can adversely impact on the ability of people with dementia to conduct basic and instrumental activities of daily living, often leaving them dependent on others for care [2, 911]. Caregivers of people with dementia are often presented with challenging and complex needs, higher levels of dependency and morbidity in the more severe stages of the condition [2, 12, 13]. People with advanced dementia often cannot participate in decision-making about their care; consequently decisions often have to be made by their caregivers (family members, friends and next of kin) [14–20].…”
Section: Introductionmentioning
confidence: 99%